2005
DOI: 10.1002/bip.20300
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates in peptide and protein design

Abstract: Monosaccharides and amino acids are fundamental building blocks in the assembly of nature's polymers. They have different structural aspects and, to a significant extent, different functional groups. Oligomerization gives rise to oligosaccharides and peptides, respectively. While carbohydrates and peptides can be found conjoined in nature, e.g., in glycopeptides, the aim of this review is the radical redesign of peptide structures using carbohydrates, particularly monosaccharides and cyclic oligosaccharides, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 89 publications
0
29
0
Order By: Relevance
“…2) were attempted to access their inhibitory efficacy on changing chemical states of termini. It has also been reported that glycopeptides could be used as therapeutic agent to design a vaccine [131] and a novel ligand [132]. Therefore, addition of glucose and deoxyglucose fragments was also considered to make IGD tripeptide specific to tumor cells, which have a high demand for glucose [133].…”
Section: De Novo Designing Of Igd As Novel Bcl-2 Inhibitorsmentioning
confidence: 99%
“…2) were attempted to access their inhibitory efficacy on changing chemical states of termini. It has also been reported that glycopeptides could be used as therapeutic agent to design a vaccine [131] and a novel ligand [132]. Therefore, addition of glucose and deoxyglucose fragments was also considered to make IGD tripeptide specific to tumor cells, which have a high demand for glucose [133].…”
Section: De Novo Designing Of Igd As Novel Bcl-2 Inhibitorsmentioning
confidence: 99%
“…Carbohydrates are promising candidates as templates for the display of functional groups due to their inherent multifunctionality, the relative rigidity of their structure, and the ease of regioselective chemical manipulation [2325]. Jensen and co-workers reported the synthesis of carbopeptides and carboproteins bearing several copies of a peptide or a protein tethered in a carbohydrate template.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are certain activated carboxylic derivatives which show enhanced reactivity and selectivity towards the amino than the hydroxyl group. In addition, in literature this synthetic methodology has been successfully applied in other examples where peptides were attached to CDs [19][20][21][22][23][24][25][26][27][28]. Another point of consideration was the short distance between the CD and the peptide if the amino CD derivative is directly attached to glycine.…”
Section: Molecular Designmentioning
confidence: 97%
“…In all previously described conjugates of other bioactive peptides with cyclodextrins [19][20][21][22][23][24][25][26][27][28], attachment of the CD unit takes place through the narrow rim of CD. In contrast, molecule 3 described in this work represents an example where a peptide skeleton is attached to CD via the large rim of CD.…”
Section: Molecular Designmentioning
confidence: 98%